Perlindungan Hukum Terhadap Hak Ekonomi Pencipta e-book Atas Proses Pendistribusian e-book Berdasarkan UU No. 28 Tahun 2014 Tentang Hak Cipta Dikaitkan Dengan UU No. 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Ruhiat Sobirin (Jurnal Media Justitia Nusantara, 2017)
The essence of copyright containing two kinds of rights, namely the right of economic and moral rights. Economic rights include the right to publish (right to publish or right to perform) and the rights to reproduce (right to copy or mechanical right). The moral rights include the author's right to have his name remarked in creation (attribution right or right of paternity) and author's rights to prohibit others destroy and mutilate his creation (right of integrity). This study uses normative juridical approach, the approach to reviewing and analyzing secondary data in the form of legal materials primary and secondary law with understanding the law as a positive set of rules or norms in the  egislation system governing human life. Based on the research note that the economic rights of the e-book Creator in accordance with the Copyright law is a copyright work produced by the creators, so that the creator has a copyright on the e-book. E-book distribution in accordance to Article 9 of the Copyright is only belongs to must be with the permission of the creator or copyright holder of the e-book, the ITE Law provides protection of economic rights of creators in terms of electronic transactions. because of the nature of the distribution of e-books using electronic media.